GRIM‐19 repressed hypoxia‐induced invasion and EMT of colorectal cancer by repressing autophagy through inactivation of STAT3/HIF‐1α signaling axis. Issue 8 (7th December 2018) - Zhang, Juan; Chu, Dake; Kawamura, Takuji; Tanaka, Kiyohito; He, Shuixiang
Abstract: Hypoxia leads to cancer progression and promotes the metastatic potential of cancer cells. Thereby, the aim of the present study was to investigate the detailed effects of gene associated with retinoid‐interferon‐induced mortality‐19 (GRIM‐19) in colorectal cancer (CRC) cell lines under hypoxia conditions and explore the potential molecular mechanisms. Here, we observed that GRIM‐19 expression was downregulated in several CRC cell lines as well as in HCT116 and Caco‐2 cells under a hypoxic microenvironment. Additionally, the introduction of GRIM‐19 obviously suppressed cell invasive ability and epithelial–mesenchymal transition (EMT) through modulating EMT markers as reflected by the upregulation of E‐cadherin along with the downregulation of vimentin and N‐cadherin under hypoxic conditions. Moreover, the addition of GRIM‐19 repressed hypoxia‐induced autophagy through modulating autophagy associated proteins as reflected by the downregulation of LC3‐II/LC3‐I ratio and Beclin‐1 expression, as well as the increased of p62 expression. Interestingly, overexpression of GRIM‐19 markedly ameliorated the accumulation of HIF‐1α triggered by hypoxia accompanied by an inhibition of vascular endothelial growth factor (VEGF) production and phospho‐signal transducer and activator of transcription 3 (p‐STAT3) expression. Further data demonstrated that GRIM‐19 have a negative feedback effect on the expression of HIF‐1α. Mechanistically, re‐expression of HIF‐1α completely reversed the inhibitory effects of GRIM‐19 on hypoxia‐induced invasion and EMT. Taken all data together, our findings established that GRIM‐19 suppresses hypoxia‐triggered invasion and EMT by inhibiting hypoxia‐induced autophagy through inactivation HIF‐1α/STAT3 signaling pathway, indicating that GRIM‐19 may serve as a potential predictive factor and therapeutic target for CRC treatment. Abstract : Gene associated with retinoid‐interferon‐induced mortality‐19 (GRIM‐19) suppresses hypoxia‐triggered invasion and EMT by inhibiting hypoxia‐induced autophagy through inactivation HIF‐1α/STAT3 signaling pathway, indicating that GRIM‐19 may serve as a potential predictive factor and therapeutic target for colorectal cancer (CRC) treatment.